# minusing summations

#### Dgphru

Hi, is this right?

If $$\displaystyle x_1 = 30 \mu + \sum_j B_j + \sum_j(xB)_{1j} = y_1$$

and

$$\displaystyle x_2 = 30 \mu + x_2 + \sum_j B_j + \sum_j(xB)_{2j} = y_2$$

then is $$\displaystyle x_1 - x_2 = - x_2 + (y_1 - y_2)$$

is that right?

coz im confused about how to minus the summations:

$$\displaystyle \sum_j(xB)_{1j} - \sum_j(xB)_{2j}$$

oh and j goes from 1..3

Last edited:

#### Defunkt

MHF Hall of Honor
Hi, is this right?

If $$\displaystyle x_1 = 30 \mu + \sum_j B_j + \sum_j(TB)_{1j} = y_1$$

and

$$\displaystyle x_2 = 30 \mu + x_2 + \sum_j B_j + \sum_j(TB)_{2j} = y_2$$

then is $$\displaystyle x_1 - x_2 = - x_2 + (y_1 - y_2)$$

is that right?

coz im confused about how to minus the summations:

$$\displaystyle \sum_j(TB)_{1j} - \sum_j(TB)_{2j}$$

oh and j goes from 1..3
What is B? What is $$\displaystyle \mu$$? What is T? We will be able to help you much more if you give the whole context of the question, or at least some more of it.

Regardless, if we assume for a second that $$\displaystyle x_1-x_2 = -x_2 + y_1 - y_2$$ then we get $$\displaystyle x_1 = y_1-y_2$$ but according to what you wrote, $$\displaystyle x_1 = y_1 \Rightarrow y_2 = 0$$... and I'm sure this isn't what you wanted.

#### Dgphru

umm, the whole question is calculate $$\displaystyle x_1 - x_2$$

when

$$\displaystyle x_i = 30\mu + 30x_i + \sum_j B_j + \sum_j (xB)_{ij} = \sum y_{i}$$

B stands for beta, and i goes from 1 to 3 and j goes from 1 to 3.